Isolation and characterization of powdery mildew-resistant Arabidopsis mutants - Vogel, John (The National Academy of Sciences, 2000)
A compatible interaction between a plant and a pathogen is the result of a complex interplay between many factors of both plant and pathogen origin. Our objective was to identify host factors involved in this interaction. These factors may include susceptibility factors required for pathogen growth, factors manipulated by the pathogen to inactivate or avoid host defenses, or negative regulators of defense responses. To this end, we identified 20 recessive Arabidopsis mutants that do not support normal growth of the powdery mildew pathogen, Erysiphe cichoracearum. Complementation analyses indicated that four loci, designated powdery mildew resistant 1–4 (pmr1–4), are defined by this collection. These mutants do not constitutively accumulate elevated levels of PR1 or PDF1.2 mRNA, indicating that resistance is not simply due to constitutive activation of the salicylic acid- or ethylene- and jasmonic acid-dependent defense pathways. Further Northern blot analyses revealed that some mutants accumulate higher levels of PR1 mRNA than wild type in response to infection by powdery mildew. To test the specificity of the resistance, the pmr mutants were challenged with other pathogens including Pseudomonas syringae, Peronospora parasitica, and Erysiphe orontii. Surprisingly, one mutant, pmr1, was susceptible to E. orontii, a very closely related powdery mildew, suggesting that a very specific resistance mechanism is operating in this case. Another mutant, pmr4, was resistant to P. parasitica, indicating that this resistance is more generalized. Thus, we have identified a novel collection of mutants affecting genes required for a compatible interaction between a plant and a biotrophic pathogen.